Pengaruh Penerapan Supervisi Akademik Berbasis Modeling Inspiratif Terhadap Peningkatan Kemampuan Mengajar Guru SD Gugus IV Kecamatan Makassar Kota Makassar - Tamrin Tamrin (JIKAP PGSD: Jurnal Ilmiah Ilmu Kependidikan, 2017)
This study aims to describe the effect of the application of one teacher movement of an innovation with an inspirational approach for elementary school teachers group IV Makassar Makassar subdistrict specifically relates to (1) Influence of inspirational model based supervision supervision on the improvement of teaching skills of elementary school teachers in cluster IV Makassar District Kota Makassar . (2) Teacher's response to inspirational model inspirational-based supervision in elementary school of group IV Makassar sub-district of Makassar City. The method of this research is quasi experiment with pre and post design using research subject as many as 62 teachers of target schools. Analysis of research result using inferential statistic on test.t (t.tes) conducted on elementary school teacher in group IV of Makassar Sub-district, Makassar City in academic year 2016/2017. The results showed that there is a significant influence on the application of inspirational modeling based academic supervision on improving teachers' teaching ability. This is seen in the significance value less than (0.00 <0.05) which means H1 (meaning there is a significant influence on the application of inspirational modeling based academic supervision on the improvement of teaching ability of elementary school teachers in group IV Makassar District Makassar City is accepted.In addition, teacher's response to the application of inspirational modeling based academic supervision is very positive